A Strategic Air Operation as one of the possible instruments in a hybrid war between the Russian Federation against Ukraine - Horbenko, Volodymyr; Korshets, Olena (Social Development and Security, 2022)
The article considers possible options for conducting a hybrid war of the Russian Federation against Ukraine. The analysis of the existing basic concepts of dysfunction of the state system is carried out. Possible options for the influence of the Russian Federation to achieve a political goal in various areas (domains) are identified based on the concepts of strategic paralysis and operation based on effects The article analyses the main factors determining the operating environment conditions in which the Air Force of the Armed Forces of Ukraine will operate. There are analysed modern forces of air attack, means of air defence, tendencies of their development, application, and influence on the present and future operating environment. The threat of conducting combined information and strategic air operation as an effective tool for achieving the political goals of the Russian Federation in Ukraine is substantiated